EKSISTENSI POPULISME PADA PEMILU PRANCIS 2017 - Rasmah Rajab; Lisda Dhyniarti Bachtiar; Mekar Sriwijayanti; Annisa Nurrahmasari; Dian Asvira (Departemen Ilmu Hubungan Internasional Univesitas Hasanuddin, 2019)
Populism is a political rhetoric that is exploited by a few people in a way that attracts sympathy from the people for a specific purpose. The concept of populism developed by theorist Ernesto Laclau can be used in analyzing populism in the 2017 elections in France. The National Front Party (FN) is the only far-right party in France founded by the famous French Populist Jeane Le Pen. The National Front is a party that has an ultrationalist and racist nature, characteristics that are far from contradicting democratic values ​​which characterize the republican government. The figure who has made FN survive until now and even passed the 2017 French elections is none other than Jeane Le Pen's own son, Marie Le Pen. Although Marine Le Pen is seen as a candidate who has no solution to the problems that exist in France, he uses anti-minority, anti-immigrant and anti-EU sentiments in his discussions. Le Pen takes the issue of SARA and points to immigrants, especially Muslims, as the cause of the economic slowdown and relatively high unemployment. Marine Le Pen brings the National Front a much